The Religious and Psychological effects of English Cartoons on children - Binesh Haseeb; Ṣabāḥat Afzal (jihat-ul-islam, 2022)
Entertainment has been a fundamental necessity for man for centuries and man has been adopting different methods for this. Human beings have been making different creative things for achieving fun. In twentieth century, television emerged as the biggest source of entertainment when the world of technology rose. With the passage of time, television industry grew and soon cartoons started appearing on television screen for children. It was a golden opportunity for the Western world to convey their social and ethical ideas to the Muslim society through their children so that they could not become part of an Islamic system or procedure. The West has trapped the present world in various things and technology mills, and the people in modern times find it almost impossible to give their children the required time. Many parents consider watching cartoons a useful activity to keep their children busy so that they may not disturb their peace of mind. It is very important to know how Western cartoons are influencing the minds of Muslim children, what is being shown in these cartoons? are things shown in cartoons permissible in Islam? And how these cartoons are altering the way Muslim children perceive Islam? All these questions have been addressed in this research study.